SIEM: Plataforma para la detección de ataques informáticos en tiempo real a partir de eventos de seguridad (2017)
This book presents the development of the degree project "Platform for the detection of computer attacks in real time from security events." The book has two main chapters corresponding to the two phases developed during the Grade Project subject, the first chapter Event Management describes the process of implementing a SIEM tool and its configuration, the second chapter shows the process of applying data science for the generation of mathematical prediction models on the events collected by SIEM tools.